Sostoyanie pechenochnoi gemodinamiki u sportsmenov vysshei kvalifikatsii - Rubtsova, M. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to reveal the status of the liver hemadynamics in dependence on the sports specialization, age sex and the training stage of the elite athletes. The athletes - national teams members (1342 males and 792 females), aged from 16 to 30 years and representing all kinds of special training process, acted as subjects. The method of rheography was used in the research. The obtained data had shown that the main peculiarities of the liver hemadynamics in athletes are refered to the level of blood filling. All the athletes demonstrated any anomalies in the rheographical inspection had demonstrated the health state anomalies.